Restoring lepidopteran diversity in a tropical dry forest: relative importance of restoration treatment, tree identity and predator pressure - Solis-Gabriel, Lizet; Mendoza-Arroyo, Wendy; Boege, Karina; del-Val, Ek (PeerJ, 2017)
Tropical dry forests (TDFs) have been widely transformed by human activities worldwide and the ecosystem services they provide are diminishing. There has been an urgent call for conservation and restoration of the degraded lands previously occupied by TDFs. Restoration experiences aim to recover species diversity and ecological functions. Different restoration strategies have been used to maximize plant performance including weeding, planting or using artificial mulching. In this investigation, we evaluated whether different restoration practices influence animal arrival and the reestablishment of biotic interactions. We particularly evaluated lepidopteran larvae diversity and caterpillar predation on plants established under different restoration treatments (mulching, weeding and control) in the Pacific West Coast of México. This study corroborated the importance of plant host identity for lepidopteran presence in a particular area. Lepidopteran diversity and herbivory rates were not affected by the restoration treatment but they were related to tree species. In contrast, caterpillar predation marks were affected by restoration treatment, with a greater number of predation marks in control plots, while caterpillar predation marks among plant species were not significantly different. This study highlights the importance of considering the introduction of high plant species diversity when planning TDF restoration to maximize lepidopteran diversity and ecosystem functioning.
Keywords: Predation rate; Clay caterpillar model; Biotic interactions; Herbivore; Mexico; Herbivory; Restoration; Management; Conservation; Insects